Impact of Silica Nanoparticles on the Durability of fly Ash Concrete - Ali, D.; Sharma, U.; Singh, R.; Singh, L. P. (Frontiers in Built Environment, 2021)
In the present study, the mechanical and durability properties of silica nanoparticle (SNP)-incorporated fly ash (FA) concrete mix were examined after 365 days of exposure. The dosages of FA replaced by cement in the present study were 30%, 40%, and 50%, while 3% SNPs were added by the weight of cement in the FA incorporated mix. For a comparison of SNPs with silica fume (SF), 6% SF was added (by the weight of cement) and entire casting was performed at a constant water to binder (w/b) ratio of 0.29. The present work is the extension of a previous study wherein durability properties of the same mixes were reported for up to 180 days of exposure. Compressive strength results show that in the presence of SNPs, the enhancement in compressive strength was in the range of 10–14%, while, in presence of SF, 8–10% of the enhancement was observed as compared to control. However, exposed samples in a carbonation environment showed that the compressive strength of the control and SF incorporated mix increased, while SNP-incorporated samples showed negligible enhancement. Further, sulphate exposed mix show that compressive strength decreases, however, the SNP-incorporated mix showed the lowest reduction compared to other mixes. Therefore, the study shows that the SNP-incorporated mix has higher mechanical properties and more durability compared to other mixes in a severe environment.